Vulnerability and Resilience Analysis by Fuzzy Cognitive Map - Tseng, Ching-Chuan (Archives of Business Research, 2019)
Risk management is one of the primary concerns in financial institutions. The study introduces the concepts of “vulnerability” and “resilience” to construct the fuzzy cognitive maps for risk evaluation. Other than exploring the type of risk that the financial institutions in Taiwan face and the level of impact caused by each type of risk, the study also investigates the relation among factors that affect the risk in financial institutions. The outcome of analysis reveals organizational culture, risk appetite, and internal audit as the most important factors affecting the vulnerability in financial institutions. The study provides a more solid risk evaluation mechanism and recommendation for the management of financial institutions as well as expand new field for financial research, enriching the new horizon for financial risk evaluation.